TINGKAT KELULUSAN HIDUP POST LARVA UDANG VANAME (Litopenaeus vannamei) YANG DIPELIHARA PADA SALINITAS RENDAH DENGAN MENGGUNAKAN METODE AKLIMATISASI BERTINGKAT - Anisa Anisa; Muhammad Marzuki; Bagus Dwi Hari Setyono; Andre Rachmat Scabra (Jurnal Perikanan Unram, 2021)
This study aims to study the graduation rate of living and post growth of vaname shrimp larvae using multilevel salinity acclimatization methods maintained at low salinity. This study consisted of five treatments, and each treatment had 3 repeats. Thus in this study there were 15 experimental units. As a treatment is the adedation period of acclimatization decreases salinity as follows: Treatment 1: No decrease in salinity (30 ppt). Treatment 2: 6 day decreased salinity (30 ppt, 24 ppt, 18 ppt, 12 ppt, 6 ppt, 0 ppt). Treatment 3: 7 days decrease in salinity (30 ppt, 25 ppt, 20 ppt, 15 ppt, 10 ppt, 5 ppt, 0 ppt). Treatment 4: 8 days decrease in salinity (30 ppt, 26 ppt, 21 ppt, 17 ppt, 13 ppt, 9 ppt, 4 ppt, 0 ppt). Treatment 5: 9 days decrease in salinity (30 ppt, 26 ppt, 23 ppt, 19 ppt, 15 ppt, 11 ppt, 8 ppt, 4 ppt, 0 ppt). The results showed that the larvae of vaname shrimp that were kept at low salinity using acclimatization methods had no noticeable effect on survival rates. The survival rate is between 72% - 94.67%, has an absolute weight between 1.75 grams – 2.36 grams and an absolute length between 1.47 cm – 1.87 cm with a fcr value of 3.17 – 3.83. The oxygen consumption rate in vaname shrimp is 1.76 – 2.2.